2013
DOI: 10.1051/0004-6361/201321465
|View full text |Cite
|
Sign up to set email alerts
|

Hi-C and AIA observations of transverse magnetohydrodynamic waves in active regions

Abstract: The recent launch of the High resolution Coronal imager (Hi-C) provided a unique opportunity of studying the EUV corona with unprecedented spatial resolution. We utilize these observations to investigate the properties of low-frequency (50−200 s) active region transverse waves, whose omnipresence had been suggested previously. The five-fold improvement in spatial resolution over SDO/AIA reveals coronal loops with widths 150−310 km and that these loops support transverse waves with displacement amplitudes <50 k… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 17 publications
(25 reference statements)
1
56
1
Order By: Relevance
“…As a starting point, we state that several recent observations of loops/spicules in groups have an apparent interstructure distance of about one tube width, see, e.g., Figure 2 (top, middle panel) and Figure 4 in Morton & McLaughlin (2013) for coronal loops and Figure 2B (bottom right corner) in De Pontieu et al (2007) for spicules. However, an intertube distance of about one tube diameter can be the result of several three-dimensional (3D) configurations (that have been integrated over the line of sight).…”
Section: Considerations On Fmentioning
confidence: 61%
See 1 more Smart Citation
“…As a starting point, we state that several recent observations of loops/spicules in groups have an apparent interstructure distance of about one tube width, see, e.g., Figure 2 (top, middle panel) and Figure 4 in Morton & McLaughlin (2013) for coronal loops and Figure 2B (bottom right corner) in De Pontieu et al (2007) for spicules. However, an intertube distance of about one tube diameter can be the result of several three-dimensional (3D) configurations (that have been integrated over the line of sight).…”
Section: Considerations On Fmentioning
confidence: 61%
“…Likewise, the energy flux estimates in transverse waves in coronal loops of 100 W m −2 reported by McIntosh et al (2011) (who calculated the energy flux using a "wave filling factor" of 100%) would be reduced to 10-20 W m −2 , using a density filling factor of 10% for their observed loop bundle. In this recalculation, we have not taken into account the claim of Morton & McLaughlin (2013) that the velocity amplitudes measured with Hi-C are smaller than the one used in McIntosh et al (2011). In the recent paper by Thurgood et al (2014), the reported energy flux of transverse waves in polar plumes of 9-24 W m −2 would be lowered to 0.9-4.8 W m −2 with our formula, again, using a density filling factor of 10%.…”
Section: Discussionmentioning
confidence: 92%
“…∼0.435 Mm) ranging in values around 0.3-0.6 Mm, and some values lower than 0.2 Mm. The reason for the sub-resolution estimation of the oscillation amplitude is the Gaussian fitting method, as pointed out also in Morton & McLaughlin (2013) using AIA and the High Resolution Coronal Imager (HI-C) data. …”
Section: åmentioning
confidence: 99%
“…Their presence over extended regions of the solar corona (Tomczyk et al 2007) may have implications on the role of waves in coronal heating. Observations with instruments such as AIA/SDO, CoMP, and Hi-C by e.g., Morton & McLaughlin (2013) and Threlfall et al (2013) have allowed us to analyse transverse oscillations with unprecedented detail.…”
Section: Introductionmentioning
confidence: 99%